Readings from the ancient Near East: primary sources for Old Testament study - Arnold, Bill T.; Beyer, Bryan (Encountering biblical studies, 2002)
Considering these works, it seems fair to say that the publisher's "Encountering Biblical Studies" series will make a useful contribution to a reader's biblical knowledge. The series, designed for undergraduate college courses in religion but useful for educated lay readers as well, is written from a very conservative or evangelical perspective and provides good examples of that approach. Aside from expository volumes like Hagner's, which address individual books of the Bible, the series consists of two surveys treating the Old and New Testaments plus two collateral volumes of readings aimed at placing the Testaments in historical context.